O seguro garantia por desempenho como mecanismo de controle dos riscos contratuais: o caso do programa Caminhos da Paraíba - Macedo, Renata Gomes de (2021)
The study aims to analyze the characteristics of the performance bond, a securitization mechanism that allows guaranteeing the quality, price and term of public works contracts. The study reviews the forms of surety for public works, highlighting the importance of these instruments as a contractual risk management tool. To illustrate the relevance of this control mechanism for public procurement, 111 public works contracts, executed between the years 2012 and 2015, were analyzed under the ―Caminhos da Paraíba‖ Program, implemented by the State Department of Highways – DER, of the Paraíba State. The results show that all contracts had term amendments, delaying, on average, the public works by 7.39 months. Moreover, 34% of the contracts had value amendments, raising the cost by R$100,519,857.97 - 16,2% of the initial cost of public works. The study concludes that the current securitization structure adopted by the ―Caminhos da Paraíba‖ Program is ineffective, and that performance bond could be a more adequate control mechanism to manage the identified risks, if there was an adequate contractual governance structure in place in the Paraíba state.